The Road to Paradise Island - Holt, Victoria, 1906-1993 (London Fontana Books, 1989)
Annalice Mallory is consumed with curiousity when she discovers the neglected grave of an ancestress with a name similar to her own. But it is her brother Philip who acts on the discovery of the long-dead Ann Alice's map and journals, and who sails in search of the legendary Paradise Island.
Keywords: Murder -- Australia -- Romance fiction